The Opportunity of Implementation STEM Education Integrated with Language Teaching in Indonesian Elementary Schools (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Education in Indonesia currently requires sufficient performance to improve abilities and skills inconducting critical discourse. To improve the ability, the performance of the community isneeded to develop the characteristic values of each individual. With STEM Education inelementary schools, the existence of an education system that provides opportunities for thecreation of humane learning and has character education values. The development of STEMbasedcharacter education values in elementary schools will be synchronized along with thedevelopment of information and communication technology which provides opportunities todevelop character education values and nationalist insights. To develop this, STEM Education inelementary schools requires efforts to improve the skills and proficiency of an individual interms of developing interests and identity. STEM Education can be taught in elementary schoolsin Indonesia, on extra-curricular materials such as robotics.